Consumer acceptance of new strawberry vinegars by preference mapping. Issue 11 (2nd November 2017) - Ubeda, C.; Callejón, R.M.; Troncoso, A.M.; Morales, M.L.
ABSTRACT: Consumers' acceptance of new strawberry vinegars was evaluated, and trained panellists described their sensory profiles. Four strawberry vinegars, three produced from puree and one from cooked must, were evaluated jointly. Due to obtaining the highest percentage of consumer acceptance, cooked strawberry must vinegar was considered to be the best. This vinegar stood out in general impression, raisin, and liqueur attributes. Internal preference maps confirmed a higher acceptance level for the strawberry vinegars over commercial vinegar. External preference mapping, obtained by PLS2 analysis, revealed that the main sensory attributes driving consumers' preferences are raisin, toasted caramel, spicy, and liqueur aroma.